Silicon-induced general, mild, and efficient one-pot, three-component synthesis of amidoalkyl naphthol libraries - Salama, Tarek A. (Synlett, 2013)
A general mild and efficient protocol for the synthesis of amidoalkyl naphthol libraries was achieved utilizing tetrachlorosilane and zinc chloride in dichloromethane at ambient temperature via a one-pot, three-component condensation of various aldehydes, nitriles (amides), and beta-naphthol.
Keywords: amidoalkyl naphthols; combinatorial synthesis; multicomponent reactions; Ritter reaction; tetrachlorosilane